Kombinasi Metode MOORA dan Rank Order Centroid dalam Sistem Pendukung Keputusan Pemilihan Supplier Produk Sepatu - Fatimah, Siti; Ardiansah, Temi (STMIK Budi Darma, 2024)
The selection of shoe product suppliers is an important process in the shoe industry, which requires careful consideration to ensure price, quality, availability, and delivery. In addition, the ability of suppliers to adapt to changing market demands and the ability to collaborate in the development of new products are also important factors. The problems that arise are uncertainty in assessing supplier quality and performance, difficulty in comparing supplier alternatives objectively, and difficulty in calculating various relevant criteria thoroughly. This study aims to apply a combination of ROC and MOORA weighting methods in determining the selection of shoe product suppliers so that it becomes a recommendation for companies in choosing the right supplier for the sustainability of the business run by the company. The combination of ROC and MOORA can provide deeper and more thorough insight into the alternatives evaluated. Using this approach, decision makers can address some of the weaknesses of each method simultaneously, resulting in more optimal and measurable decisions. The use of a combination of ROC and MOORA can help organizations in achieving their goals in a more efficient and effective manner. The recommendation for the selection of shoe product suppliers shows the ranking results of each supplier based on the final value of the MOORA and ROC calculations, the ranking results show rank 1 with a value of 0.093 obtained by Supplier F, rank 2 with a value of 0.0827 obtained by Supplier A and Supplier E, and rank 3 with a value of 0.0458 obtained by Supplier H.